2017
DOI: 10.1590/1980-5373-mr-2017-0717
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Duplex Stainless steel (UNS S31803) Powders Obtained by high Energy Milling of Chips with Additions of NbC

Abstract: In this study, the high energy mechanical milling was utilized to the production of duplex stainless steel powders from the recycling chips with and without the addition niobium carbide. The effect of milling time and addition carbide on the morphology, particle size and magnetic properties of the powders was investigated. The utilization of the powder metallurgy constitute an important alternative for the reuse of waste in the industrial sector. The milling was realized using a planetary ball mill for 20 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The presence of deformation-induced martensite was also observed. Mendonça et al (2017) verified the appearance of the martensite induced by deformation after the milling process, by increasing the values of saturation magnetization obtained by magnetic measurements [22].…”
Section: Microhardness (Hv)supporting
confidence: 62%
See 1 more Smart Citation
“…The presence of deformation-induced martensite was also observed. Mendonça et al (2017) verified the appearance of the martensite induced by deformation after the milling process, by increasing the values of saturation magnetization obtained by magnetic measurements [22].…”
Section: Microhardness (Hv)supporting
confidence: 62%
“…verified an increase in density values for the duplex stainless-steels starting from Fe-Cr-Ni powders produced by powder metallurgy at temperatures of Thus, the particle size obtained after 50 h of milling with 3% vanadium carbide was the measurement by particle size analyzer and was found to be smaller than the initial chip size. Mendonça et al (2017) show that the addition of carbides increases the efficiency of the milling process over carbide-free milling-this is due to the carbide particles, a material with a high hardness, which collides with the chip. This collision causes a region of generalized stresses in the ductile particle, leading to rupture through the combination of the ductile-brittle process [40].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors revealed the production of finer particles, d 50 of almost 100 µm, by the addition of SA in the beginning of the milling process [ 8 ]. As regards the fragmentation in the presence of reinforcement, an addition of a 3% NbC resulted in narrowing particle size distribution [ 28 ].…”
Section: Characterization Of Powder Particles Produced From Metal Chipsmentioning
confidence: 99%
“…Thus, grain coarsening did not occur in the annealed nanocomposite powders, at 600 °C for 1 h, whereas the milled-annealed Ti 6 Al 4 V powders showed significant grain coarsening [ 27 ]. Other researchers evaluated the recycling of a duplex stainless steel in the presence of 3% of NbC by milling, the transformation of austenite to martensite occurred, induced by severe plastic deformation though that transformation reduced in the presence of NbC [ 28 ]. Some researchers produced in situ TiC reinforced Ti composite powder by adding graphite to Ti chips; these authors showed that the graphite behaved as an inhibitor for fragmentation as well as oxidation [ 31 ].…”
Section: Recycling Chips For Powder Metallurgy Applicationsmentioning
confidence: 99%
“…Vanadium carbide is an important material for industrial applications due to excellent resistance to high temperatures, and its high chemical and thermal stability, even at high temperature [17]. In some studies, it was verified that the addition of carbide in the process of the high energy milling of chips from the machining process, resulted in greater efficiency of the milling process, with a greater decrease in the size of the particles, obtaining sizes of nanometric particles [18][19][20].…”
Section: Introductionmentioning
confidence: 99%